Perceived environmental correlates of cycling for transport among adults in five regions of Europe. (January 2016) - Mertens, L.; Compernolle, S.; Gheysen, F.; Deforche, B.; Brug, J.; Mackenbach, J. D.; Lakerveld, J.; Oppert, J.‐M.; Feuillet, T.; Glonti, K.; Bárdos, H.; De Bourdeaudhuij, I.
Summary: Regular cycling for transport is an important potential contributor to daily physical activity among adults. Characteristics of the physical environment are likely to influence cycling for transport. The current study investigated associations between perceived physical environmental neighbourhood factors and adults' cycling for transport across five urban regions across Europe, and whether such associations were moderated by age, gender, education and urban region. A total of 4, 612 adults from five European regions provided information about their transport‐related cycling and their neighbourhood physical environmental perceptions in an online survey. Hurdle models adjusted for the clustering within neighbourhoods were performed to estimate associations between perceived physical environmental neighbourhood factors and odds of engaging in cycling for transport and minutes of cycling for transport per week. Inhabitants of neighbourhoods that were perceived to be polluted, having better street connectivity, having lower traffic speed levels and being less pleasant to walk or cycle in had higher levels of cycling for transport. Moderation analyses revealed only one interaction effect by gender. This study indicates that cycling for transport is associated with a number of perceived physical environmental neighbourhood factors across five urban regions across Europe. Our results indicated that the majority of the outcomes identified were valid for all subgroups of age, gender, education and across regions in the countries included in the study.